Are patient education and self‐care advantageous for patients with head and neck cancer? A feasibility study - Anne Söderlund Schaller; Elena Dragioti; Gunilla M. Liedberg; Britt Larsson (Wiley, 2019)
Abstract Aim This study evaluates whether patient education and individually self‐care reduces pain and improves QoL, mood and sleep during and after radiotherapy treatment for patients with head and neck cancer. Design A longitudinal, two‐armed feasibility study design was performed. Methods Sixty‐four participants with curative intent were included in the study. All participants answered questions about pain three times a week and completed a survey questionnaire about pain, QoL, psychological aspects and barriers towards pain management at baseline, at 4 weeks and at 10 weeks. Thirty‐four of the participants attended in two education sessions on pain based on their beliefs about pain and received individualized self‐care instructions based on their weekly rating of pain. Result This study did not find any significant group differences for the pain, QoL, mood and sleep.